The Expansion of Production, Marketing and Consumption of Chat in Ethiopia (Global Journal of Science Frontier Research, 2017)
Chat (Catha edulis) is a plant of uncertain and very debatable status grown in Ethiopia. The chewing of chat leaves has a deep-rooted religious and socio-cultural tradition. It is considered a cash crop and source of economic value to the societies and nations involved. However, there have been reports of negative economic effects on the individuals engaging in the habit of chat chewing. The paper discusses the increasing importance of chat as a major cash crop in the Ethiopian and the controversies that its production and marketing generates. It also presents and discusses the results of the CSA and Revenue data through summarizing. The results of the review show the opportunities and challenges related to chat production and export to Ethiopia’s neighboring countries in the process of internationalization. The strategic and policy implications of the results are also addressed. Chat export earnings about 10% share with annual growth of 17.4%
Keywords: chat; economy; dilemma; constraints